2005
DOI: 10.1128/jvi.79.6.3500-3508.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Stoichiometry of Antibody Neutralization of Human Immunodeficiency Virus Type 1

Abstract: The human immunodeficiency virus envelope glycoproteins function as trimers on the viral surface, where they are targeted by neutralizing antibodies. Different monoclonal antibodies neutralize human immunodeficiency virus type 1 (HIV-1) infectivity by binding to structurally and functionally distinct moieties on the envelope glycoprotein trimer. By measuring antibody neutralization of viruses with mixtures of neutralizationsensitive and neutralization-resistant envelope glycoproteins, we demonstrate that the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
142
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(148 citation statements)
references
References 84 publications
6
142
0
Order By: Relevance
“…We inferred that one 2F5 antibody molecule was sufficient when its epitope was in functional SU or TM because X2Y1 and X1Y2 species were neutralized with equal efficiency and neutralization occurred even at DNA ratios at which most heterotrimers would carry a single 2F5 epitope. The same conclusion has been reached by others (37,43). We previously showed that the 2F5 antibody slightly inhibited but did not prevent virions with 2F5 epitopes in SU from binding to cells with the mCAT1 receptor (25).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We inferred that one 2F5 antibody molecule was sufficient when its epitope was in functional SU or TM because X2Y1 and X1Y2 species were neutralized with equal efficiency and neutralization occurred even at DNA ratios at which most heterotrimers would carry a single 2F5 epitope. The same conclusion has been reached by others (37,43). We previously showed that the 2F5 antibody slightly inhibited but did not prevent virions with 2F5 epitopes in SU from binding to cells with the mCAT1 receptor (25).…”
Section: Discussionsupporting
confidence: 65%
“…Different antibodies may have different mechanisms. Stoichiometry of antibody binding for neutralization has been extensively studied, but debate about how many antibody molecules need to bind per virion for neutralization continues (4,16,17,37,43).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their model applies to antibodies differing in neutralizing potency and to virus isolates with different neutralization sensitivities. 13 There is yet another group of functional antibodies that do not neutralize the virus but may exert protective efficacy by inducing antibody dependent cell cytotoxicity (ADCC) i.e., they direct the killing of infected cells through recognition of viral proteins on cell surfaces.…”
Section: Mechanisms Of Antibody Mediated Protectionmentioning
confidence: 99%
“…It is difficult to reconcile binding of a large Ab (150 kDa) to a small surface glycoprotein (46 kDa) without loss of protein function. Indeed, for HIV-1, a compelling argument has been made that if an Ab binds to the wildtype envelope complex, it will neutralize (54)(55)(56)(57). Consistent with this notion, a heterologous Ab can inhibit and neutralize HIV-1 infectivity when the epitope recognized by that Ab is engineered into the gp120 subunit of HIV-1 envelope (56, 57).…”
Section: Discussionmentioning
confidence: 78%